Possible Myiothlypis flaveola (Baird, 1865) and M. leucophrys (Pelzeln, 1868) (Passeriformes: Parulidae) hybrids - de Godoy, Fernando Igor; Gabriel, Vagner de Araujo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
We report on a possible hybrid between two congeners, Myiothlypis flaveola and M. leucophrys, that have not been found to hybridize previously. On January 29, 2015, an individual with intermediate plumage between M. flaveola and M. leucophrys was captured in a mist net in a forest restoration area in the municipality of Piracicaba, São Paulo state, Brazil. The same individual was recaptured and observed in the field, where it was possible to record its song to compare with its purported parental species.
Keywords: Hybridization; Southeastern Brazil; Taxonomy; Warbler